'I'm just ringing to get a repeat prescription for my contraceptive pill, doctor': developing authentic simulated telephone consultations for medical students. Issue 5 (3rd September 2021) - Beddows, Julie; Abdalla, Magdy; Blanchard, David; Hammond, Ellie; Hay, Fiona; Webb, Matthew; Protheroe, Joanne
ABSTRACT: Within normal surgery hours telephone consultations have been previously shown to make up between 10–20% of patient contacts with General Practitioners (GPs) and to comprise a large proportion of a GP's daily workload. Although obviously very useful, such doctor–patient interactions can be fraught with risk. The General Medical Council (GMC) requires that newly graduated doctors should be adaptable to the challenge of delivering treatment advice and management remotely. Yet, currently, there is limited specific training in telephone consultation skills in both undergraduate and postgraduate curricula. Authentic and properly supervised exposure of medical students to GP telephone consultations can be difficult to achieve in clinical placements. Therefore, we have developed emergency telephone consultations within our primary care Safe and Effective Clinical Outcomes (SECO) clinics which are simulated GP surgeries organised for our final year students. We have expanded the range of patients presenting in these clinics by including trained, simulated patients requesting an urgent telephone consultation with a GP. In doing so we aim to enhance our student's skills and confidence in conducting telephone consultations. This teaching exchange paper aims to describe the ideas behind the construction of simulated patient telephone scripts together with the difficulties and successes encountered in introducing telephone consultations into our GP SECO clinic. We hope these ideas and processes will stimulate and enable others to help students prepare for this challenging area of clinical medicine made increasingly significant by the Covid-19 pandemic.